1994
DOI: 10.1002/ps.2780420307
|View full text |Cite
|
Sign up to set email alerts
|

The toxicity of three second‐generation rodenticides to Barn Owls

Abstract: The toxicity of three second‐generation rodenticides to Barn Owls (Tyto alba Scop.) has been investigated. Brodifacoum, difenacoum and flocoumafen were separately fed to owls over a period of 15 days via rodenticide‐fed mice to simulate the potential route of exposure in the wild. The owls survived a cumulative dose of each rodenticide of at least 1.9 mg kg−1 owl body weight over 15 days. This is equivalent to the consumption of two 25 g mice with a rodenticide residue of 1 mg kg−1 each day for 15 days. Residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
2
1

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 5 publications
0
24
2
1
Order By: Relevance
“…The HB rats subjected to a 20-d feeding test had a mean whole-carcass residue of 0.738 Ϯ 0.040 mg/kg body weight. The values obtained were considerably lower than those previously reported in the literature for mice (up to 5.15 mg/kg body wt) in studies concerning the toxicity of difenacoum residues to owls [17]. The methodology used in the present study was very similar to that used by Gray et al [17], but because of the lower residues detected, we explored several adaptations of the method (e.g., different solvent combinations, protease digestion, Soxhlet extraction).…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…The HB rats subjected to a 20-d feeding test had a mean whole-carcass residue of 0.738 Ϯ 0.040 mg/kg body weight. The values obtained were considerably lower than those previously reported in the literature for mice (up to 5.15 mg/kg body wt) in studies concerning the toxicity of difenacoum residues to owls [17]. The methodology used in the present study was very similar to that used by Gray et al [17], but because of the lower residues detected, we explored several adaptations of the method (e.g., different solvent combinations, protease digestion, Soxhlet extraction).…”
Section: Resultscontrasting
confidence: 73%
“…A review of the published studies concerning the residues of second‐generation anticoagulant rodenticides in rodents is given in Table 3. Employing methods very similar to those used in the present study (solvent extraction and HPLC analysis), Gray et al [17] found that the whole‐carcass residue of difenacoum in mice fed 50 mg/kg bait ad libitum for 2 d and then killed immediately was 5.15 mg/kg body weight. Thus, it would appear that the whole‐carcass residue of difenacoum as parent compound was either lower in rats compared to mice or had a greater binding capacity and, therefore, increased refractory proportion.…”
Section: Discussionmentioning
confidence: 93%
“…This finding was confirmed by Newton et al (1990,1994) who also found that the risk potential of flocoumafen was lower compared with brodifacoum. However, when controlling the dose of the rodenticide received by barn owls, it appeared that the toxicity of difenacoum, flocoumafen and brodifacoum was of the same order of magnitude (Gray et al, 1992). Tests carried out by Pank & Hirata (1976) on mongooses (Herpestes auropunctatus) proved that difenacoum and possibly brodifacoum may be judged somewhat more favourably than bromadiolone or chlorophacinone, although the concentration of active substance contained in the N Sterner (1978) N Sterner ( Jobsen (1978) (13-90) U m 'The ferret counted as 'dead' actually recovered from moribund state after treatment with antidot.…”
Section: Discussion Of the Study Resultsmentioning
confidence: 91%
“…Today, many LC-MS-MS techniques are available to detect minute amounts of AVKs in various biological samples such as the liver, plasma or fecal samples (Jin et al, 2008, Vandenbroucke et al, 2008bSage et al, 2010, Vudathala et al, 2010. We have even shown that non-invasive monitoring, as already suggested by Gray et al (1994) on pellets of birds of prey could easily use fecal samples of foxes for instance: it is possible to confirm exposure even one month after the last ingestion of a www.intechopen.com…”
Section: Secondary Toxicitymentioning
confidence: 92%